2024
DOI: 10.3389/fpls.2023.1322238
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mechanism of seed dormancy in Symplocos paniculata

Qiaoyu Tang,
Yunzhu Chen,
Lijuan Jiang
et al.

Abstract: Symplocos paniculata is a highly desirable oil species for biodiesel and premium edible oil feedstock. While germplasm preservation and breeding are crucial, the severity of seed dormancy poses a challenge to successful germination. We employed S. paniculata seeds as experimental materials and conducted an investigation into the types and causes of seed dormancy by analyzing the morphology and developmental characteristics of its embryo, exploring the water permeability property of the endocarp, and examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Glabra) seeds with a purity level of ≥97.0%, moisture content of ≤7.0%, and a germination rate of ≥85.0% were procured. Chinese cabbage seeds are frequently utilized in experiments to validate seed dormancy inhibitors, given their non-dormant characteristics, high germination rate, straightforward germination process, and short germination cycle [21].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Glabra) seeds with a purity level of ≥97.0%, moisture content of ≤7.0%, and a germination rate of ≥85.0% were procured. Chinese cabbage seeds are frequently utilized in experiments to validate seed dormancy inhibitors, given their non-dormant characteristics, high germination rate, straightforward germination process, and short germination cycle [21].…”
Section: Plant Materialsmentioning
confidence: 99%
“…The seed of S. paniculata , however, exhibits a profound dormancy-induced state, resulting in a significantly sluggish and feeble germination capacity. Under natural conditions, the prolonged dormancy process leads to a significant loss of viability in most S. paniculata seeds, resulting in formidable barriers to seed propagation and severely limiting its potential for cultivation [ 11 , 12 ]. Therefore, it is imperative to systematically investigate dormancy release mechanisms and develop rapid methods to enhance germination of S. paniculata seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable endeavors [ 13 , 14 ] have been undertaken in recent decades to comprehend the pathways governing seed dormancy release, whether induced by external environmental factors or the inherent characteristics of seeds. The previous studies [ 7 , 11 ] have demonstrated that the seed-coat (endocarp) of S. paniculata seeds exhibits hardness and impermeability, while metabolic inhibitors were also detected in the endosperm. Inherent dormancy in woody species such as Cornus florida [ 15 ], Pinus bungeana [ 16 ], Tilia henryana [ 17 ], Saraca asoca [ 18 ] and Jatropha sinensis [ 19 ] are controlled by maternal structures and embryo physiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation